A case of complete remission of intractable gestational choriocarcinoma with subsequent chemotherapy after pembrolizumab - Kaoru Niimi; Eiko Yamamoto; Yukari Oda; Yuki Nishiko; Mayu Shibata; Kimihiro Nishino; Hiroaki Kajiyama (Elsevier, 2023)
Objective: Gestational choriocarcinoma is a gestational trophoblastic neoplasia (GTN) that originates from abnormal trophoblast proliferation. Although chemotherapy is effective for choriocarcinoma, personalized treatment becomes essential when patients develop chemoresistance. Here, we present the clinical course of a case of intractable choriocarcinoma that achieved complete remission with pembrolizumab following cytotoxic chemotherapy. Case report: A 38-year-old woman was initially diagnosed with low-risk GTN and treated with single- and multi-agent chemotherapy. She underwent a hysterectomy and was diagnosed with pathological choriocarcinoma with high-risk GTN. She was treated with multiple courses of several chemotherapy regimens. However, she did not achieve remission. Her choriocarcinoma showed high microsatellite instability; therefore, she took ten courses of pembrolizumab, but her hCG value increased. Subsequently, she underwent eight courses of paclitaxel and carboplatin alternating with paclitaxel and etoposide and achieved remission. Conclusion: This case suggests that pembrolizumab may improve the efficacy of subsequent chemotherapy.